2013
DOI: 10.1111/aas.12068
|View full text |Cite
|
Sign up to set email alerts
|

Pain characteristics and management of inpatients admitted to a comprehensive cancer centre: a cross‐sectional study

Abstract: Approximately two thirds of inpatients reported pain and one third had breakthrough pain. A substantial number of patients with pain were left untreated. Opioid-treated patients reported highest pain intensity and number of breakthrough episodes; however, analgesic medication seemed to be underused. Measures to improve pain assessment and management are highly required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Maintaining the dose of oxycodone and increasing the pregabalin dose improved pain control and reduced side effects relative to oxycodone dose titration with maintenance of pregabalin dose [56]. Despite the evidence, adjuvant medications are underutilized in practice, and in certain series, adjuvants were used in less than 50 % of patients treated for cancer pain [57][58][59]. A systematic review of eight prospective clinical studies showed that the combination of adjuvant analgesic drugs (such as antidepressants or antiepileptic) with opioids for cancer pain is not as effective as it is in non-cancer neuropathic pain [60].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining the dose of oxycodone and increasing the pregabalin dose improved pain control and reduced side effects relative to oxycodone dose titration with maintenance of pregabalin dose [56]. Despite the evidence, adjuvant medications are underutilized in practice, and in certain series, adjuvants were used in less than 50 % of patients treated for cancer pain [57][58][59]. A systematic review of eight prospective clinical studies showed that the combination of adjuvant analgesic drugs (such as antidepressants or antiepileptic) with opioids for cancer pain is not as effective as it is in non-cancer neuropathic pain [60].…”
Section: Introductionmentioning
confidence: 99%
“…3,17,18 Pain was identified as the most common problem (27.8%) that was presented by the cancer patients visiting the emergency department in northern Taiwan. 19 The inadequate pain management as measured by negative Pain Management Index (PMI) were also reported by Mitera 20 with 25% in patients with pain related to bone metastasis, and by Fisch 21 with 33% in patients with pain related to various cancer diagnosis and receiving care in ambulatory setting.…”
Section: Undertreatment Of Cancer Painmentioning
confidence: 99%
“…[74,75] In a recent study of 134 cancer pain patients, BTP episodes were reported by 30.5%. [76] In a retrospective study of consecutive pain patients at a single center, 56.4% of patients overall reported severe BTP; in cancer pain patients, 70.3% reported severe BTP. [77] These numbers may actually under-report the phenomenon, in that the definition of BTP has recently been challenged to include "BTP-like flares" in patients who do not have chronic background pain controlled by opioids.…”
Section: The Role Of Ir Oxycodonementioning
confidence: 99%